Patient awareness and role in attaining healthcare quality: A qualitative, exploratory study - Wudma Alemu; Eshetu Girma; Tefera Mulugeta (Elsevier, 2021)
Background: Healthcare quality, a critical component of healthcare services, is a demanding product of the joint efforts of the healthcare stakeholders; yet, the quality of health care is often lower than expected. It has been reported that patients who feel empowered play an important role in the quality of care delivery. In Ethiopia, no study has examined healthcare quality from the patient's perspective. In this study, we explored whether or not patients were aware of healthcare quality, as well as their role in improving the quality of care. Method: This descriptive, exploratory study included in-depth interviews with 12 inpatients using a semi-structured interview guide. Participants were recruited from the inpatient units of a large referral hospital in Addis Ababa, Ethiopia using purposive sampling with maximum variation. Field notes were collected and interviews were audio-recorded. Data were coded, transcribed verbatim, translated into English, and analyzed thematically using OpenCode. Results: All participants were aware of problems with healthcare quality and occurrence of medical errors. Most participants rated healthcare quality as poor or marginally good. Participants did not know their role in the pursuit of healthcare quality; most assumed a passive role in care delivery. Conclusion: Overall, study participants were not satisfied with the quality of their care during hospitalization. Patient satisfaction can be improved through patient empowerment and engagement in the care delivery process.